A low - power down - converter mixer applied to the UHF transceivers - Nguyen, Hoàng Đức; Ho, Quang Tây (Journal of Technical Education Science, 2014)
Frequency translation in a system is performed by a non-linear device known as a mixer. The most popular double-balanced mixer used in RFIC designs is the Gilbert Cell mixer. This mixer is an individual block of a 433 MHz transceiver. The proposed mixer requires a 1.8V supply voltage and consumed a 2.88mA current. The third-order intercept point and noise figure are-2.43 dBm and 8.9 dB. The excellent LO/RF and RF/IF isolations are also up to 147 dB and 109dB, respectively.